Subunit-specific synaptic delivery of AMPA receptors by auxiliary chaperone proteins TARPγ8 and GSG1L in classical conditioning. (3rd April 2017) - Keifer, Joyce; Tiwari, Neeraj K.; Buse, Leah; Zheng, Zhaoqing
Highlights: Mechanisms for subunit-selective AMPAR trafficking in learning is poorly understood. Sequential delivery of GluA1 and GluA4 AMPARs underlies classical conditioning. TARPγ8 chaperones GluA1-containing AMPARs while GSG1L chaperones GluA4 subunits. Auxiliary proteins regulate sequential AMPAR synaptic delivery in conditioning. Abstract: AMPA receptor (AMPAR) trafficking has emerged as a fundamental concept for understanding mechanisms of learning and memory as well as many neurological disorders. Classical conditioning is a simple and highly conserved form of associative learning. Our studies use an ex vivo brainstem preparation in which to study cellular mechanisms underlying learning during a neural correlate of eyeblink conditioning. Two stages of AMPAR synaptic delivery underlie conditioning utilizing sequential trafficking of GluA1-containing AMPARs early in conditioning followed by replacement with GluA4 subunits later. Subunit-selective trafficking of AMPARs is poorly understood. Here, we focused on identification of auxiliary chaperone proteins that traffic AMPARs. The results show that auxiliary proteins TARPγ8 and GSG1L are colocalized with AMPARs on abducens motor neurons that generate the conditioning. Significantly, TARPγ8 was observed to chaperone GluA1-containing AMPARs during synaptic delivery early in conditioning while GSG1L chaperones GluA4 subunits later in conditioning. Interestingly, TARPγ8 remains at the membrane surface as GluA1 subunits are withdrawn and associates with GluA4 when they are delivered to synapses. These data indicate that GluA1- and GluA4-containing AMPARs are selectively chaperoned by TARPγ8 and GSG1L, respectively. Therefore, sequential subunit-selective trafficking of AMPARs during conditioning is achieved through the timing of their interactions with specific auxiliary proteins.